Digitalization Improves the Creative Economy in Islamic Economic Perspective - Sutrisno, S; Sampurno, Feri D.; Mahendra, Yusril Ihza; Fitriyah, Hadiah (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
This abstract discusses the potential of digital economy and creative industries in the context of Islamic economics and ethics, particularly in Indonesia. The background of the study is the development of local wisdom and creative industries to support the global economy. The research problem is the challenges faced in implementing digital economy, particularly in relation to Islamic economic principles. The aim of the study is to explore the application of Islamic Work Ethic (IWE) in the context of digital economy and creative industries. The methodology involves a literature review of works on digital economy and Islamic economics. The findings highlight the potential of digital economy in promoting growth in creative industries within the framework of Islamic economics. The implications include the need to apply Islamic ethical principles in digital economy and creative industries, as well as the importance of understanding the challenges and risks involved.